Does the Carbon Emissions Trading Policy Increase Corporate Tax Avoidance? Evidence from China - Feng, Chen; Zhu, Xingshu; Gu, Yu; Liu, Yuecheng (Frontiers in Energy Research, 2022)
Based on the natural experiment of carbon emissions trading pilots in China, this paper investigates the effect of environmental regulation on corporate tax avoidance. The results show that: 1) Market-incentivized environmental regulation significantly increase the level of corporate tax avoidance. 2) Heterogeneity analysis shows that the effect is more obvious on the non-state-owned firms, firms with severe financing constraints, and firms in highly competitive industries. 3) We find that the reduction of cash flow is the channel for environmental regulation to affect corporate tax avoidance. 4) Further analysis shows that government subsidies can alleviate the enhancement of tax avoidance by environmental regulation. The more government subsidies a company receives, the less tax avoidance it has.